Manajemen Strategi Dewan Kemakmuran Masjid dalam Meningkatkan Kesadaran Beragama Jama’ah di Kabupaten Subang - Fahmi, Mochammad; Sadiah, Dewi; Aziz, Ali (Tadbir: Jurnal Manajemen Dakwah, 2025)
This study examines the formulation, implementation, and evaluation of the mosque prosperity council using qualitative descriptive methods. The theory used is David, Fred R. The results of the study indicate that: First, the formulation is carried out through mapping the spiritual needs of the congregation and SWOT analysis to formulate policies based on priority scales. Second, Implementation includes routine religious study programs, youth development, social services, and PHBI. Third, Evaluation is carried out by measuring the level of congregation participation and the effectiveness of the program in increasing religious awareness. Overall, the Strategic Management implemented has succeeded in increasing religious awareness, as evidenced by the increasing participation of the congregation in various programs, although there are still obstacles in the consistency of attendance.